First records of Little Stint Calidris minuta in Indonesia - Muzika, Yann; Yong, Ding Li; Chowdhury, Sayam U; Putra, Chairunas Adha (KUKILA, 2020)
Details are presented of the first two Indonesian records of the Little Stint Calidris minuta, discovered during shorebird surveys on the north coast of Aceh Province, Sumatra, between 18 October 2019 and 30 January 2020. As the species has already been recorded multiple times in most of the surrounding countries it is assumed that it had hitherto been overlooked in Indonesia. As further records from other parts of Indonesia can be expected, we summarise key features for distinguishing the species from the very similar Red-necked Stint Calidris ruficollis, with which it often associates.